Counterparty Credit Limit: Identifikasi, Pengukuran dan Pemetaan Risiko Bank-Bank di Indonesia - Saur Costanius Simamora (Research Center and Case Clearing House PPM School of Management, 2021)
This study aims to carry out risk management planning, identification, qualitative analysis and quantitative risk calculations, establishing counterparty credit limits on banks in Indonesia. The risk identification process utilize 59 expert views from the field of financial institution banks in Indonesia. Subsequently the qualitative analysis stage employ the two dimension rating schemes method, namely probability and impact. Each included risk is measured in the Low, Medium and High category. The identification process resulted in 18 risks that are facing banks in Indonesia. From that risks, the quantitative analysis using Probability - Impact dimension shows that in the Low - Medium quadrant there is 1 risk. In the Medium - Medium quadrant there are 3 risks. In the Medium-High quadrant there are 8 risks. While the High - High quadrant resulted in 6 risks. The Delphi method output from the probability dimension, indicates the risk of error in analyzing the counterparty's financial performance (balance sheet analysis, cashflow, income statement, financial ratio) and not monitoring and recognizing sanctions or legal cases that occur to counterparties give a value of 2.29. While from the Impact dimension, the risk of error in analyzing the counterparty's financial performance (balance analysis, R / L report, financial ratio) give a value of 2.78. All of these results, the experts have reached convergence or consensus.